Lithium ion battery layer oxygen positive electrode material and preparation method and application thereof

By sintering the precursor of the lithium-ion battery positive electrode material, a metal fluoride coating is formed, which solves the problem of inaccurate distribution of doping elements in the prior art, and improves the capacity and cycle stability of the lithium-ion battery.

CN119517956AActive Publication Date: 2025-02-25XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411616663.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode material doping technology cannot effectively improve the capacity and cycle life of lithium-ion batteries, and the distribution of doped elements is inaccurate, resulting in performance not meeting expectations.

Method used

By sintering the precursor of the positive electrode material, a metal fluoride coating with different concentration ratios of double F/M` is formed to improve element utilization, reduce internal defects of matrix particles, and enhance structural stability and compressive resistance.

Benefits of technology

It improves the capacity and circulation stability of lithium-ion batteries, reduces the side reaction between the material and the electrolyte, reduces the corrosion of trace HF on the material, and improves the circulation performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132407130000141
    Figure BDA0005132407130000141
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion batteries, and particularly relates to a lithium ion battery layer oxygen positive electrode material and a preparation method and application thereof. The preparation method of the lithium ion battery layer oxygen positive electrode material comprises the following steps: uniformly mixing an M source, an M source and a lithium source, carrying out high-temperature calcination on the obtained mixture in an oxygen-containing gas environment, and carrying out low-temperature calcination on the high-temperature calcination product in a fluorine-containing gas environment, the volume fraction of fluorine in the fluorine-containing gas is more than 3%, and the lithium ion battery layer oxygen positive electrode material is obtained. And after the low-temperature calcination is finished, introducing inert gas and naturally cooling to room temperature to obtain the oxygen positive electrode material of the lithium ion battery layer. The lithium ion battery layer oxygen positive electrode material obtained by the method provided by the invention can effectively improve the capacity and the cycle life of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion batteries, and in particular relates to a lithium ion battery layer oxygen positive electrode material and a preparation method and application thereof. Background Art

[0002] As one of the four key materials of lithium-ion batteries, cathode materials play a vital role in the final performance of lithium-ion batteries. Element doping is a common method to stabilize the crystal structure of cathode materials and improve safety performance. It is usually done by adding a small amount of impurity atoms or ions to the cathode materials to change the electronic structure, ion diffusion path and crystal stability of the materials, thereby improving the capacity and cycle life of lithium-ion batteries.

[0003] For the doping of positive electrode materials, the traditional method is usually to introduce doping elements during the precursor sintering process, or to introduce doping elements after the positive electrode material is formed and perform high-temperature sintering. However, this usually cannot achieve precise control over the distribution of doping elements, and it is easy for some elements to fail to enter the crystal structure of the material, resulting in the positive electrode material performance not meeting expectations or even deteriorating. Summary of the invention

[0004] The first purpose of the present invention is to overcome the defect that the existing doped positive electrode material cannot effectively improve the capacity and cycle life of lithium ion batteries, and to provide a new lithium ion battery layer oxygen positive electrode material, which can effectively improve the capacity and cycle life of lithium ion batteries.

[0005] The second object of the present invention is to provide a method for preparing a lithium ion battery.

[0006] The third object of the present invention is to provide a lithium ion battery layer oxygen positive electrode material prepared by the above method.

[0007] The fourth object of the present invention is to provide application of the above-mentioned lithium ion battery layer oxygen positive electrode material in lithium ion batteries.

[0008] Specifically, the lithium-ion battery layer oxygen positive electrode material provided by the present invention comprises a substrate, a first region located on the surface of the substrate, and a second region located on the surface of the first region; the chemical formula of the substrate is Li 1+m M a M` b O 2 , the chemical formula of the first region and the second region is Li 1+m M a M` b O 2-c F c, M is selected from at least one of Ni, Co and Mn, M` is selected from at least one of Al, Mg, Sr, Zr, Ba, Ti, Ca and rare earth elements, a+b=1, 0.9≤a≤1, 0<b≤0.1, -0.05≤m≤0.1, 0<c≤0.1; the matrix does not contain free doping element M`; the ratio of the atomic concentration of F to the atomic concentration of M` in the first region is less than the ratio of the atomic concentration of F to the atomic concentration of M` in the second region, the first region contains a region where the ratio of the atomic concentration of F to the atomic concentration of M` is less than 0.5, and the second region contains a region where the ratio of the atomic concentration of F to the atomic concentration of M` is greater than 1.

[0009] The preparation method of the lithium ion battery layer oxygen positive electrode material provided by the present invention comprises the steps of uniformly mixing an M source, an M` source and a lithium source, and then subjecting the obtained mixture to high-temperature calcination in an oxygen-containing gas environment, and then subjecting the high-temperature calcination product to low-temperature calcination in a fluorine-containing gas environment, wherein the volume fraction of fluorine gas in the fluorine-containing gas is more than 3%, and after the low-temperature calcination is completed, an inert gas is introduced and the temperature is naturally cooled to room temperature to obtain the lithium ion battery layer oxygen positive electrode material.

[0010] The key to the present invention is to add a low-temperature platform to carry out fluorine-containing gas treatment after the positive electrode material precursor is sintered, and at the same time control the proportion of fluorine gas in the fluorine-containing gas, so that a more electronegative F element can be introduced on the surface of the positive electrode material matrix as a "target point", and the free elements that are not doped into the lattice inside the matrix are pulled to the surface of the matrix particles, and a double metal fluoride coating layer with different F / M' atomic concentration ratios is formed on the surface of the matrix particles. This can not only improve the element utilization rate, reduce the internal defects of the matrix particles, and improve the structural stability and compressive resistance of the material, but also the internal M' element doping of the matrix particles and the double co-coating of the external M' element and F element can synergistically improve the capacity of the lithium-ion battery. At the same time, the formation of the double metal fluoride coating layer with different F / M' atomic concentration ratios can also effectively reduce the side reaction between the material and the electrolyte, reduce the corrosion of the material by trace HF in the battery system, and improve the cycle performance of the material. In addition, the present invention provides F element through fluorine gas, and the content of F element introduced into the material is controlled by the content of free elements in the material that are not doped into the matrix lattice, and the F element will not be introduced excessively. The free elements dispersed in the matrix are attracted by the external fluorine environment, and most of them are enriched on the surface of the matrix particles. Therefore, the F content on the surface is relatively high. At the same time, affected by the diffusion dynamics, a small part of the F element will also diffuse into the inside of the matrix particles and combine with the free elements. Therefore, the final state is that the surface layer of the matrix particles has a higher F element than the near-surface layer. In addition, the method provided by the present invention uses fluorine gas as the doping gas, and no other impurity elements are introduced except fluorine gas.

[0011] In a preferred embodiment, the low-temperature calcination method is to introduce inert gas to evacuate the oxygen-containing gas and reduce the temperature to the low-temperature calcination temperature after the high-temperature calcination is completed, and then introduce fluorine-containing gas for low-temperature calcination, that is, a low-temperature platform is added to the cooling section after the high-temperature calcination to carry out low-temperature calcination of fluorine-containing gas. At this time, the elements in the matrix particles that are not doped into the lattice are still in an activated state, which is conducive to being drawn to the surface of the particles by the fluorine element to participate in the fluorination reaction, and the capacity and cycle performance of the material are better. DETAILED DESCRIPTION

[0012] The lithium-ion battery layer oxygen positive electrode material provided by the present invention comprises a substrate, a first region and a second region. The first region is located on the surface of the substrate, and the second region is located on the surface of the first region. That is, the surface of the substrate is sequentially coated with the first region and the second region.

[0013] In the present invention, the chemical formula of the matrix is ​​Li 1+m M a M` b O 2 , the chemical formula of the first region and the second region is Li 1+m M a M` b O 2-c F c, M is selected from at least one of Ni, Co and Mn, M' is selected from at least one of Al, Mg, Sr, Zr, Ba, Ti, Ca and rare earth elements, a+b=1, 0.9≤a≤1, 0<b≤0.1, -0.05≤m≤0.1, 0<c≤0.1. Specifically, the matrix can be at least one of lithium cobalt oxide, ternary materials (nickel cobalt manganese), lithium-rich manganese-based materials and layered lithium manganese oxide. M' is a doping element, which is selected from at least one of Al, Mg, Sr, Zr, Ba, Ti, Ca and rare earth elements, preferably at least one of Mg, Al and Ti. When M' is preferably at least one of Mg, Al and Ti, these elements are more easily drawn to the particle surface when they exist in a free state, which is more conducive to avoiding the generation of internal defects of the matrix particles and better improving the cycle stability or rate performance of the material. The term "rare earth element" includes lanthanides, scandium (Sc) and yttrium (Y). Wherein, the lanthanide element is selected from at least one of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu). a can be 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1 or any value therebetween. b can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value therebetween. m can be -0.05, -0.04, -0.03, -0.02, -0.01, 0, 0.01, 0.02, 0.04, 0.06, 0.08, 0.1 or any value therebetween. c can be 0.01, 0.02, 0.04, 0.06, 0.08, 0.1 or any value therebetween. In addition, the particle size D50 of the matrix is ​​preferably 2 to 20 μm, specifically 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm or any value therebetween.

[0014] In the present invention, both the first region and the second region contain F element and M` element, and the ratio of the atomic concentration of F to the atomic concentration of M` in the first region is less than the ratio of the atomic concentration of F to the atomic concentration of M` in the second region. The first region contains a region where the ratio of the atomic concentration of F to the atomic concentration of M` is less than 0.5. Preferably, the ratio of the atomic concentration of F to the atomic concentration of M` in the first region is 0.2 to 0.5, and can be specifically 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or any value therebetween. The second region contains a region where the ratio of the atomic concentration of F to the atomic concentration of M` is greater than 1. Preferably, the ratio of the atomic concentration of F to the atomic concentration of M` in the second region is 1 to 4, and can be specifically 1, 1.5, 2, 2.5, 3, 3.5, 4 or any value therebetween. In addition, the thickness of the first region is preferably 10-50 nm, specifically 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm or any value therebetween. The thickness of the second region is preferably 2-5 nm, specifically 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm or any value therebetween.

[0015] The preparation method of the lithium ion battery layer oxygen positive electrode material provided by the present invention comprises the steps of uniformly mixing an M source, an M` source and a lithium source, and then subjecting the obtained mixture to high-temperature calcination in an oxygen-containing gas environment, and then subjecting the high-temperature calcination product to low-temperature calcination in a fluorine-containing gas environment, wherein the volume fraction of fluorine gas in the fluorine-containing gas is more than 3%, and after the low-temperature calcination is completed, an inert gas is introduced and the temperature is naturally cooled to room temperature to obtain the lithium ion battery layer oxygen positive electrode material.

[0016] In the present invention, the stoichiometric ratio of the M source, M' source and lithium source is such that the chemical formula of the obtained matrix is ​​Li 1+ m M a M` b O 2, M is selected from at least one of Ni, Co and Mn, M' is selected from at least one of Al, Mg, Sr, Zr, Ba, Ti, Ca and rare earth elements, a+b=1, 0.9≤a≤1, 0<b≤0.1, -0.05≤m≤0.1. M' is a doping element selected from at least one of Al, Mg, Sr, Zr, Ba, Ti, Ca and rare earth elements, preferably at least one of Mg, Al and Ti. The term "rare earth element" includes lanthanides, scandium (Sc) and yttrium (Y). Wherein, the lanthanide element is selected from at least one of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu). a can be 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1 or any value therebetween. b can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value therebetween. m can be -0.05, -0.04, -0.03, -0.02, -0.01, 0, 0.01, 0.02, 0.04, 0.06, 0.08, 0.1 or any value therebetween.

[0017] The present invention does not particularly limit the type of M source, and can be any existing substance that can react with a lithium source to form a positive electrode material. For example, it can be selected from at least one of the oxides, hydroxides, oxyhydroxides, carbonates, oxalates, and acetates of M, or the oxides, hydroxides, oxyhydroxides, carbonates, oxalates, and acetates of M doped with M'. Specifically, it can be listed as the hydroxides, oxyhydroxides, carbonates, oxalates, and acetates of Ni, the hydroxides, oxyhydroxides, carbonates, oxalates, and acetates of Co, the hydroxides, oxyhydroxides, carbonates, oxalates, and acetates of Mn, the hydroxides, oxyhydroxides, carbonates, oxalates, and acetates of Ni doped with Al, and the hydroxides, oxyhydroxides, carbonates, oxalates, and acetates of Al doped with Ni. The hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Co; the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Mn doped with Al; the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Ni doped with Mg; the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Co doped with Mg; the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Mn doped with Mg; the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Ni doped with Sr; the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Co doped with Sr; the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Mn doped with Sr hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Ni doped with Zr, hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Co doped with Zr, hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Mn doped with Zr, hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Ni doped with Ba, hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Co doped with Ba, hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Mn doped with Ba, hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Ni doped with Ti, hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Co doped with Ti at least one of the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Ti-doped Mn, the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Ca-doped Ni, the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Ca-doped Co, the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Ca-doped Mn, the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Ni doped with rare earth elements, the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Co doped with rare earth elements, and the hydroxide, oxyhydroxide, carbonate, oxalate, acetate of Mn doped with rare earth elements.

[0018] The present invention has no particular limitation on the type of M' source, and can be any existing material that can be used as a doping element to improve the capacity and cycle performance of a lithium-ion battery. For example, it can be selected from at least one of oxides, carbonates, hydroxides, nitrates, oxalates, chlorides, fluorides, sulfates, and acetates containing M', such as oxides, carbonates, hydroxides, nitrates, oxalates, chlorides, fluorides, sulfates, and acetates of Al, oxides, carbonates, hydroxides, nitrates, oxalates, chlorides, fluorides, sulfates, and acetates of Mg, oxides, carbonates, hydroxides, nitrates, oxalates, chlorides, fluorides, sulfates, and acetates of Sr, , fluoride, sulfate, acetate; oxide, carbonate, hydroxide, nitrate, oxalate, chloride, fluoride, sulfate, acetate of Zr; oxide, carbonate, hydroxide, nitrate, oxalate, chloride, fluoride, sulfate, acetate of Ba; oxide, carbonate, hydroxide, nitrate, oxalate, chloride, fluoride, sulfate, acetate of Ti; oxide, carbonate, hydroxide, nitrate, oxalate, chloride, fluoride, sulfate, acetate of Ca; oxide, carbonate, hydroxide, nitrate, oxalate, chloride, fluoride, sulfate, acetate of rare earth elements.

[0019] The present invention has no particular limitation on the type of lithium source, which can be selected from at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium sulfate and lithium bicarbonate.

[0020] In the present invention, the oxygen-containing gas may be oxygen or a mixed gas of oxygen and an inert gas. The oxygen concentration in the oxygen-containing gas is preferably 20 to 100 vol%, specifically 20 vol%, 25 vol%, 30 vol%, 35 vol%, 40 vol%, 45 vol%, 50 vol%, 55 vol%, 60 vol%, 65 vol%, 70 vol%, 75 vol%, 80 vol%, 85 vol%, 90 vol%, 95 vol%, 100 vol% or any value therebetween.

[0021] In the present invention, the fluorine-containing gas is a mixed gas of fluorine gas and an inert gas. The volume fraction of the fluorine gas is 3% or more, preferably 3-10%, and specifically can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. When the volume fraction of fluorine gas in the fluorine-containing gas is lower than 3%, the fluorine content will not be sufficient to completely extract the elements in the matrix particles that are not doped into the crystal lattice, the material capacity will not change much, and the cycle performance cannot be effectively improved.

[0022] In the present invention, the conditions for high temperature calcination include a temperature preferably of 800-1100°C, such as 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C or any value therebetween; and a time preferably of 6-20h, such as 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h or any value therebetween.

[0023] In the present invention, the conditions of the low-temperature calcination include a temperature of preferably 500-750°C, such as 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or any value therebetween; the time is preferably 2-6h, such as 2h, 3h, 4h, 5h, 6h or any value therebetween. In a preferred embodiment, the low-temperature calcination is carried out by introducing an inert gas to exhaust the oxygen-containing gas and lowering the temperature to the low-temperature calcination temperature after the high-temperature calcination is completed, and then introducing a fluorine-containing gas for low-temperature calcination. If the temperature is completely reduced to room temperature and then raised to the calcination temperature required for low-temperature calcination, the elements that are not doped into the matrix lattice will exist in the matrix particles in a relatively stable chemical state. After the temperature is raised again, this part of the doped elements cannot be fully activated to participate in the fluorination reaction, and the effect is poor. On the contrary, directly adding a low-temperature platform for calcination during the cooling process can pull the undoped elements in the matrix particles to the surface of the matrix particles when they are still in an activated state, giving the material a higher capacity and better cycle stability. In addition, the rate of decreasing the high calcination temperature to the low calcination temperature is preferably 0.4-5°C / min, specifically 0.4, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5°C / min or any value therebetween.

[0024] In the present invention, the inert gas may be nitrogen and / or argon.

[0025] The present invention also provides a lithium ion battery layer oxygen positive electrode material prepared by the method.

[0026] In addition, the present invention also provides the use of the above-mentioned lithium ion battery layer oxygen positive electrode material in lithium ion batteries.

[0027] The present invention will be described in detail below through examples.

[0028] Example 1

[0029] According to Li 1.01 Co 0.99 Mg 0.01 O 2Cobalt trioxide, magnesium carbonate and lithium carbonate are weighed respectively in a stoichiometric ratio and mixed evenly. The resulting mixture is then calcined at 1000°C for 10 h in a mixed atmosphere of oxygen and nitrogen (containing 30 vol% oxygen), nitrogen is introduced to evacuate the oxygen-containing gas and the temperature is lowered to 650°C at a rate of 0.4°C / min, and then a mixed atmosphere of fluorine and nitrogen (the volume fraction of fluorine is 6%) is introduced, and the mixture is calcined for 4 h. After the calcination is completed, nitrogen is introduced and the mixture is naturally cooled to room temperature, and the layered oxygen positive electrode material for lithium-ion batteries is obtained after sieving and powdering.

[0030] The lithium-ion battery layer oxygen positive electrode material includes a substrate, a first region located on the surface of the substrate, and a second region located on the surface of the first region. The results of laser particle size analyzer, scanning electron microscope (SEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) show that the particle size D50 of the substrate is 19.4μm, the substrate does not contain free doping element Mg, the first region and the second region both contain F element and Mg element, the ratio of the atomic concentration of F to the atomic concentration of Mg in the first region is 0.2-0.5, the ratio of the atomic concentration of F to the atomic concentration of Mg in the second region is 1-4, the thickness of the first region is 34-36nm, and the thickness of the second region is 3-4nm. In addition, XPS is used to test the atomic concentrations of F element and doping element Mg at 1nm and 10nm on the surface of the material, and the ratio is calculated. The results are shown in Table 1.

[0031] Example 2

[0032] According to Li 1.01 Co 0.99 Mg 0.01 O 2 Cobalt trioxide, magnesium carbonate and lithium carbonate are weighed in a stoichiometric ratio and mixed evenly. The resulting mixture is then calcined at 800°C for 20 hours in a mixed atmosphere of oxygen and nitrogen (containing 30 vol% oxygen), nitrogen is introduced to evacuate the oxygen-containing gas and the temperature is lowered to 500°C at a rate of 5°C / min, and then a mixed atmosphere of fluorine and nitrogen (the volume fraction of fluorine is 3%) is introduced, and the mixture is calcined for 6 hours. After the calcination is completed, nitrogen is introduced and the mixture is naturally cooled to room temperature, and the layered oxygen positive electrode material for lithium-ion batteries is obtained after sieving and powdering.

[0033] The lithium-ion battery layer oxygen positive electrode material includes a substrate, a first region located on the surface of the substrate, and a second region located on the surface of the first region. The results of the laser particle size analyzer, SEM and XPS show that the particle size D50 of the substrate is 16.5μm, the substrate does not contain free doping element Mg, the first region and the second region both contain F element and Mg element, the ratio of the atomic concentration of F to the atomic concentration of Mg in the first region is 0.2-0.5, the ratio of the atomic concentration of F to the atomic concentration of Mg in the second region is 1-4, the thickness of the first region is 30-33nm, and the thickness of the second region is 2.5-3.5nm. In addition, XPS is used to test the atomic concentrations of F element and doping element Mg at 1nm and 10nm on the surface of the material, and the ratio is calculated. The results are shown in Table 1.

[0034] Example 3

[0035] According to Li 1.01 Co 0.99 Mg 0.01 O 2 Cobalt trioxide, magnesium carbonate and lithium carbonate are weighed respectively in a stoichiometric ratio and mixed evenly. The resulting mixture is then calcined at 1000°C for 10 h in a mixed atmosphere of oxygen and nitrogen (containing 30 vol% oxygen), nitrogen is introduced to evacuate the oxygen-containing gas and the temperature is lowered to 750°C at a rate of 2°C / min, and then a mixed atmosphere of fluorine and nitrogen (the volume fraction of fluorine is 10%) is introduced, and the mixture is calcined for 2 h. After the calcination is completed, nitrogen is introduced and the mixture is naturally cooled to room temperature, and the lithium-ion battery layer oxygen positive electrode material is obtained after sieving and powdering.

[0036] The lithium-ion battery layer oxygen positive electrode material includes a substrate, a first region located on the surface of the substrate, and a second region located on the surface of the first region. The results of the laser particle size analyzer, SEM, XRD and XPS show that the particle size D50 of the substrate is 11.2μm, the substrate does not contain free doping element Mg, the first region and the second region both contain F element and Mg element, the ratio of the atomic concentration of F to the atomic concentration of Mg in the first region is 0.2-0.5, the ratio of the atomic concentration of F to the atomic concentration of Mg in the second region is 1-4, the thickness of the first region is 35-37nm, and the thickness of the second region is 3.5-4.5nm. In addition, XPS is used to test the atomic concentrations of F element and doping element Mg at 1nm and 10nm on the surface of the material, and the ratio is calculated. The results are shown in Table 1.

[0037] Example 4

[0038] According to LiCo 0.99 Al 0.01 O 2Cobalt trioxide, aluminum oxide and lithium carbonate are weighed respectively in a stoichiometric ratio and mixed evenly. The resulting mixture is then calcined at 1000°C for 10 hours in a mixed atmosphere of oxygen and nitrogen (containing 30 vol% oxygen), nitrogen is introduced to evacuate the oxygen-containing gas and the temperature is lowered to 650°C at a rate of 3°C / min, and then a mixed atmosphere of fluorine and nitrogen (the volume fraction of fluorine is 6%) is introduced, and the mixture is calcined for 4 hours. After the calcination is completed, nitrogen is introduced and the mixture is naturally cooled to room temperature, and the lithium-ion battery layer oxygen positive electrode material is obtained after sieving and powdering.

[0039] The lithium-ion battery layer oxygen positive electrode material includes a substrate, a first region located on the surface of the substrate, and a second region located on the surface of the first region. The results of the laser particle size analyzer, SEM, XRD and XPS show that the particle size D50 of the substrate is 10.5μm, the substrate does not contain free doping element Al, the first region and the second region both contain F element and Al element, the ratio of the atomic concentration of F to the atomic concentration of Al in the first region is 0.2-0.5, the ratio of the atomic concentration of F to the atomic concentration of Al in the second region is 1-4, the thickness of the first region is 46-48nm, and the thickness of the second region is 4-5nm. In addition, XPS is used to test the atomic concentrations of F element and doping element Al at 1nm and 10nm on the surface of the material, and the ratio is calculated. The results are shown in Table 1.

[0040] Example 5

[0041] According to Li 0.99 Co 0.99 Ti 0.01 O 2 Cobalt trioxide, titanium dioxide and lithium carbonate are weighed respectively in a stoichiometric ratio and mixed evenly. The resulting mixture is then calcined at 1000°C for 10 h in a mixed atmosphere of oxygen and nitrogen (containing 30 vol% oxygen), nitrogen is introduced to evacuate the oxygen-containing gas and the temperature is lowered to 650°C at a rate of 3°C / min, and then a mixed atmosphere of fluorine and nitrogen (the volume fraction of fluorine is 6%) is introduced, and the mixture is calcined for 4 h. After the calcination is completed, nitrogen is introduced and the mixture is naturally cooled to room temperature, and the layered oxygen positive electrode material for lithium-ion batteries is obtained after sieving and powdering.

[0042] The lithium-ion battery layer oxygen positive electrode material includes a substrate, a first region located on the surface of the substrate, and a second region located on the surface of the first region. The results of the laser particle size analyzer, SEM, XRD and XPS show that the particle size D50 of the substrate is 9.2μm, the substrate does not contain free doping element Ti, the first region and the second region both contain F element and Ti element, the ratio of the atomic concentration of F to the atomic concentration of Ti in the first region is 0.2-0.5, the ratio of the atomic concentration of F to the atomic concentration of Ti in the second region is 1-4, the thickness of the first region is 27-29nm, and the thickness of the second region is 2-3nm. In addition, XPS is used to test the atomic concentrations of F element and doping element Ti at 1nm and 10nm on the surface of the material, and the ratio is calculated. The results are shown in Table 1.

[0043] Example 6

[0044] The layered oxygen positive electrode material for lithium-ion batteries was prepared according to the method of Example 1, except that after high-temperature calcination, the material was cooled to room temperature before low-temperature calcination. The specific steps are as follows:

[0045] According to Li 1.01 Co 0.99 Mg 0.01 O 2 Cobalt trioxide, magnesium carbonate and lithium carbonate were weighed and mixed in a stoichiometric ratio, and the resulting mixture was calcined at 1000°C for 10 h in a mixed atmosphere of oxygen and nitrogen (containing 30 vol%), and then naturally cooled to room temperature to obtain a matrix Li 1.01 Co 0.99 Mg 0.01 O 2 A mixed atmosphere of fluorine and nitrogen (the volume fraction of fluorine is 6%) is introduced into the substrate, the temperature is raised to 650°C and calcined for 4 hours, nitrogen is introduced after the calcination is completed and the temperature is naturally cooled to room temperature, and the lithium-ion battery layer oxygen positive electrode material is obtained after sieving and powdering.

[0046] The lithium-ion battery layer oxygen positive electrode material includes a substrate, a first region located on the surface of the substrate, and a second region located on the surface of the first region. The results of the laser particle size analyzer, SEM, XRD and XPS show that the particle size D50 of the substrate is 19.4μm, the substrate does not contain free doping element Mg, the first region and the second region both contain F element and Mg element, the ratio of the atomic concentration of F to the atomic concentration of Mg in the first region is 0.2-0.5, the ratio of the atomic concentration of F to the atomic concentration of Mg in the second region is 1-4, the thickness of the first region is 34-36nm, and the thickness of the second region is 3-4nm. In addition, XPS is used to test the atomic concentrations of F element and doping element Mg at 1nm and 10nm on the surface of the material, and the ratio is calculated. The results are shown in Table 1.

[0047] Comparative Example 1

[0048] A lithium-ion battery layer oxygen positive electrode material was prepared according to the method of Example 2, except that the volume fraction of fluorine gas in the mixed atmosphere was reduced to 1%. The other conditions were the same as in Example 2, and a lithium-ion battery layer oxygen positive electrode material was obtained. The matrix particles of the lithium-ion battery layer oxygen positive electrode material contained the doping element Mg.

[0049] Comparative Example 2

[0050] The lithium ion battery layer oxygen positive electrode material was prepared according to the method of Example 2, except that the mixed gas of fluorine gas and nitrogen gas was replaced by nitrogen gas. The other conditions were the same as those of Example 2 to obtain the lithium ion battery layer oxygen positive electrode material.

[0051] Comparative Example 3

[0052] A lithium-ion battery layer oxygen positive electrode material is prepared according to the method of Example 1, except that the fluorine gas in the mixed atmosphere is replaced by hydrogen fluoride (HF) of the same volume fraction, and the other conditions are the same as in Example 1, to obtain a lithium-ion battery layer oxygen positive electrode material, which contains only a very thin fluorine-containing layer on the outer surface.

[0053] Comparative Example 4

[0054] The lithium ion battery layer oxygen positive electrode material was prepared according to the method of Example 1, except that the fluorine gas in the mixed atmosphere was replaced by trifluoromethane (CHF 3 ) is replaced, and the other conditions are the same as in Example 1, to obtain a lithium ion battery layer oxygen positive electrode material, which only contains a very thin fluorine-containing layer on the outer surface.

[0055] Comparative Example 5

[0056] The lithium ion battery layer oxygen positive electrode material was prepared according to the method of Example 1, except that the fluorine gas in the mixed atmosphere was replaced by hexafluoroethane (C 2 F 6 ) is replaced, and the other conditions are the same as in Example 1, to obtain a lithium ion battery layer oxygen positive electrode material, which only contains a very thin fluorine-containing layer on the outer surface.

[0057] Comparative Example 6

[0058] The lithium ion battery layer oxygen positive electrode material was prepared according to the method of Example 1, except that the fluorine gas in the mixed atmosphere was replaced by carbon tetrafluoride (CF 4 ) is replaced, and the other conditions are the same as in Example 1, to obtain a lithium ion battery layer oxygen positive electrode material, which only contains a very thin fluorine-containing layer on the outer surface.

[0059] Comparative Example 7

[0060] The layered oxygen positive electrode material for lithium-ion batteries is prepared according to the method of Example 1, except that the temperature is first cooled to room temperature after high-temperature calcination and then low-temperature calcination is performed, and the mixed atmosphere containing fluorine gas is replaced by ammonium fluoride. The specific steps are as follows:

[0061] According to Li 1.01 Co 0.99 Mg 0.01 O 2 Cobalt trioxide, magnesium carbonate and lithium carbonate were weighed and mixed in a stoichiometric ratio, and the resulting mixture was calcined at 1000°C for 10 h in a mixed atmosphere of oxygen and nitrogen (containing 30 vol%), and then naturally cooled to room temperature to obtain a matrix Li 1.01 Co 0.99 Mg 0.01 O 2 The matrix and ammonium fluoride are mixed evenly, and then the temperature is raised to 650°C for calcination for 4 hours. After the calcination is completed, nitrogen is introduced and the temperature is naturally cooled to room temperature. After sieving and powdering, a lithium ion battery layer oxygen positive electrode material is obtained. The matrix particles of the lithium ion battery layer oxygen positive electrode material contain the doping element Mg.

[0062] Comparative Example 8

[0063] The layered oxygen positive electrode material for lithium-ion batteries is prepared according to the method of Example 2, except that the high-temperature calcination is followed by cooling to room temperature before low-temperature calcination, and the mixed atmosphere containing fluorine gas is replaced by magnesium fluoride. The specific steps are as follows:

[0064] According to Li 1.01 Co 0.99 Mg 0.01 O 2 Cobalt trioxide, magnesium carbonate and lithium carbonate were weighed and mixed in a stoichiometric ratio, and the resulting mixture was calcined at 1000°C for 10 h in a mixed atmosphere of oxygen and nitrogen (containing 30 vol%), and then naturally cooled to room temperature to obtain a matrix Li 1.01 Co 0.99 Mg 0.01 O 2 The matrix and magnesium fluoride are mixed evenly, and then the temperature is raised to 500°C for calcination for 6 hours. After the calcination is completed, nitrogen is introduced and the temperature is naturally cooled to room temperature. After sieving and powdering, a lithium ion battery layer oxygen positive electrode material is obtained. The matrix particles of the lithium ion battery layer oxygen positive electrode material contain the doping element Mg.

[0065] Test Case

[0066] The positive electrode materials obtained in the above examples and comparative examples were mixed with conductive carbon and flux PVDF in a weight ratio of 90:5:5 in NMP and then coated on aluminum foil to obtain a pole piece. The pole piece was dried in a blast oven at 80°C and then placed in a vacuum oven at 120°C to dry overnight. The dried pole piece was rolled and used as a positive electrode of the battery (with a compaction density of 4.2 g / cm 3 ), lithium metal as the battery negative electrode, a single-layer polyethylene film as the separator, 1M LiPF6-EC-EMC (that is, the concentration of LiPF6 in EC-EMC solvent is 1M, EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 3:7) as the electrolyte, assembled into a 2032 battery for electrochemical testing.

[0067] (1) Gram capacity: After the unactivated battery was left at 25°C for 6 hours, it was charged at a constant current of 0.1C to a cut-off voltage of 4.6V, then charged at a constant voltage to a cut-off current of 0.01C, and then discharged at a constant current of 0.1C to a cut-off voltage of 3.0V. The discharge capacity was divided by the mass of the active material (i.e., the lithium cobalt oxide positive electrode material) to obtain the gram capacity of the positive electrode material. The battery was charged and discharged once more in the same manner, and the battery at this time was regarded as an activated battery. The results are shown in Table 1.

[0068] (2) Cycle retention rate: Using activated batteries, charge and discharge cycles were performed 50 times at 45°C, at a current density of 0.5C, and in a voltage range of 3.0 to 4.6V to examine the capacity retention rate of the positive electrode material. The results are shown in Table 1.

[0069] (3) Compression resistance: The BET growth rate of the material after 180 MPa compression is used to characterize it. The material with a smaller growth rate has better compression resistance: A powder hydraulic press is used to recover the powder after 180 MPa pressure maintenance for 30 seconds, and the BET growth rate of the material after compression is tested and calculated. The results are shown in Table 1.

[0070]

[0071] It can be seen from the results of Examples 1 to 6 that the method provided by the present invention is used to prepare lithium-ion battery layer oxygen positive electrode materials. The lithium-ion battery layer oxygen positive electrode materials obtained under different fluorine gas treatment conditions and different doping elements not only have higher gram capacity and cycle retention rate, but also have good compressive resistance.

[0072] From the comparison between Example 1 and Example 6, it can be seen that when a low-temperature platform is added to the cooling stage after high-temperature calcination to carry out low-temperature calcination with fluorine-containing gas, the capacity and cycle performance of the obtained material are better.

[0073] From the comparison between Example 2 and Comparative Example 1, it can be seen that when the fluorine gas volume fraction in the fluorine-containing gas is too low, the fluorine content is insufficient to extract all the elements in the material that are not doped into the crystal lattice, and the material capacity does not change much, but the compressive performance deteriorates significantly and the cycle performance decreases.

[0074] From the comparison between Example 2 and Comparative Example 2, it can be seen that if the fluorination treatment is not performed, the capacity, cycle performance and compressive resistance of the material will be significantly deteriorated.

[0075] From the comparison between Example 1 and Comparative Examples 3 to 6, it can be seen that when other fluorine-containing gases are used instead of fluorine gas, it is difficult to achieve the fluorination effect, and the capacity, cycle performance and compressive resistance of the material are all poor.

[0076] From the comparison between Example 1 and Comparative Example 7, and Example 2 and Comparative Example 8, it can be seen that when fluoride is directly coated on the surface of the base particles, the elements in the material that are not doped into the crystal lattice cannot be drawn to the surface, the compressive properties of the material cannot be improved, and the capacity and cycle performance deteriorate significantly.

[0077] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A lithium ion battery layer oxygen positive electrode material, characterized in that: The lithium-ion battery layer oxygen positive electrode material comprises a substrate, a first region located on the surface of the substrate, and a second region located on the surface of the first region; the chemical formula of the substrate is Li 1+m M a M` b O2, the chemical formula of the first region and the second region is Li 1+m M a M` b O 2-c F c , M is selected from at least one of Ni, Co and Mn, M` is selected from at least one of Al, Mg, Sr, Zr, Ba, Ti, Ca and rare earth elements, a+b=1, 0.9≤a≤1, 0<b≤0.1, -0.05≤m≤0.1, 0<c≤0.1; the matrix does not contain free doping element M`; the ratio of the atomic concentration of F to the atomic concentration of M` in the first region is less than the ratio of the atomic concentration of F to the atomic concentration of M` in the second region, the first region contains a region where the ratio of the atomic concentration of F to the atomic concentration of M` is less than 0.5, and the second region contains a region where the ratio of the atomic concentration of F to the atomic concentration of M` is greater than 1.

2. The lithium-ion battery layer oxygen positive electrode material according to claim 1, characterized in that: The ratio of the atomic concentration of F to the atomic concentration of M' in the first region is 0.2-0.5; the ratio of the atomic concentration of F to the atomic concentration of M' in the second region is 1-4.

3. The lithium-ion battery layer oxygen positive electrode material according to claim 1, characterized in that: The particle size D50 of the matrix is ​​2-20 μm; the thickness of the first region is 10-50 nm, and the thickness of the second region is 2-5 nm.

4. A method for preparing a lithium-ion battery layer oxygen positive electrode material, characterized in that: The method comprises uniformly mixing an M source, an M` source and a lithium source, and then subjecting the obtained mixture to high-temperature calcination in an oxygen-containing gas environment, and then subjecting the high-temperature calcination product to low-temperature calcination in a fluorine-containing gas environment, wherein the volume fraction of fluorine gas in the fluorine-containing gas is more than 3%, and after the low-temperature calcination is completed, an inert gas is introduced and the temperature is naturally cooled to room temperature to obtain a lithium-ion battery layer oxygen positive electrode material.

5. The method for preparing the lithium-ion battery layer oxygen positive electrode material according to claim 4, characterized in that: The stoichiometric ratio of the M source, M' source and lithium source is such that the chemical formula of the obtained matrix is ​​Li 1+m M a M` b O2, M is selected from at least one of Ni, Co and Mn, M' is selected from at least one of Al, Mg, Sr, Zr, Ba, Ti, Ca and rare earth elements, a+b=1, 0.9≤a≤1, 0<b≤0.1, -0.05≤m≤0.1; Preferably, the M source is selected from at least one of an oxide, hydroxide, oxyhydroxide, carbonate, oxalate, acetate of M, or an oxide, hydroxide, oxyhydroxide, carbonate, oxalate, acetate of M doped with M'; Preferably, the M' source is selected from at least one of oxides, carbonates, hydroxides, nitrates, oxalates, chlorides, fluorides, sulfates and acetates containing M'; Preferably, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium sulfate and lithium bicarbonate.

6. The method for preparing the layered oxygen positive electrode material for lithium-ion batteries according to claim 4, characterized in that: The oxygen concentration in the oxygen-containing gas is 20-100 vol%; the volume fraction of fluorine in the fluorine-containing gas is 3-10%.

7. The method for preparing the layered oxygen positive electrode material for lithium-ion batteries according to claim 4, characterized in that: The high temperature calcination conditions include a temperature of 800 to 1100° C. and a time of 6 to 20 hours.

8. The method for preparing the layered oxygen positive electrode material for lithium-ion batteries according to claim 4, characterized in that: The low-temperature calcination method is to introduce inert gas after the high-temperature calcination is completed to evacuate the oxygen-containing gas and reduce the temperature to the low-temperature calcination temperature, and then introduce fluorine-containing gas for low-temperature calcination; Preferably, the rate of decreasing the high temperature calcination temperature to the low temperature calcination temperature is 0.4-5°C / min; Preferably, the low-temperature calcination conditions include a temperature of 500 to 750° C. and a time of 2 to 6 hours.

9. A lithium-ion battery layer oxygen positive electrode material prepared by the method according to any one of claims 4 to 8.

10. Use of the lithium ion battery layer oxygen positive electrode material according to any one of claims 1 to 3 and 9 in lithium ion batteries.

Citation Information

Patent Citations

  • Method for preparing gas-phase fluorine-doped modified high-nickel cathode material through gradient sintering

    CN109638251A

  • Fluorine ion gradient doped lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

    CN114420920A

  • Manufacturing method of positive-electrode active material, and manufacturing method of lithium secondary cell

    JP2009087891A